Effect of di-(2-ethylhexyl) phthalate on N-cadherin and catenin protein expression in rat testis - Sobarzo, Cristian Marcelo (2006)
This study investigated the effect of DEHP exposure on N-cadherin and -, - and p120-catenin immunoreactivities in the rat testis. DEHP was administered by daily gavage to 25-day-old male Sprague–Dawley rats at a dose of 2 g DEHP/5 ml corn oil/kg body weight for 2 days or 7 days. Control rats were treated with corn oil vehicle under the same conditions. Animals were killed at 24 h after the last treatment. Another group of rats treated with DEHP or corn oil vehicle (control group) for 2 days were held for 30 days without treatment to observe recovery. Testes were analyzed for histopathology, TUNEL staining, immunofluorescence (IF) and Western blot analyses. Animals exposed to DEHP for 2 days or 7 days showed severe alterations of seminiferous tubules characterized by germ cell sloughing. Animals from the longer term recovery group treated with DEHP showed foci of delayed spermatogenesis. A linear and continuous pattern of N-cadherin was observed in the basal compartment of the seminiferous tubules. A similar pattern but with higher IF intensity was observed for N-cadherin in rats treated with DEHP for 2 days or 7 days, compared to control animals. The -, - and p120-catenins were detected in the basal compartment of seminiferous tubules in similar localization and IF pattern for DEHP and control groups. A significant increase in testicular N-cadherin and -catenin levels was detected by Western blot analysis in DEHP-exposed versus control rats. No variations in N-cadherin or catenin expression were detected in the recovery groups. These findings demonstrate that DEHP induces an up-regulation of N-cadherin and -catenin expression and may perturb cell–cell adhesion phenomena in the seminiferous tubule.